The Role of Good Corporate Governance in Cross-Border Halal Supply Chain Management: Ensuring Transparency, Compliance, and Sustainable Growth - Hana Luthfia Widi; Baginda Parsaulian (ICIEFS Proceeding, 2025)
This article examines the pivotal role of good corporate governance (GCG) in managing cross-border halal supply chains to ensure product integrity, compliance with Islamic law, transparency, and sustainable business practices. Halal supply chains that operate across international borders encounter numerous complexities, including diverse halal certification standards, logistic risks, potential contamination, and infrastructure disparities. These challenges necessitate stringent governance frameworks to maintain halal authenticity and foster consumer trust. The study highlights how GCG principles such as accountability, risk management, ethical conduct, and stakeholder engagement enhance traceability and compliance throughout the global halal supply chain. Furthermore, the integration of modern technologies like blockchain and adherence to environmental, social, and governance (ESG) criteria contribute to the sustainability and resilience of halal supply chains. Case studies from countries with strong halal governance frameworks, notably Indonesia, demonstrate how effective regulation and corporate governance can optimize halal supply chain operations while supporting ethical business growth. This comprehensive analysis underscores that the fusion of good corporate governance with halal principles is essential for overcoming international trade challenges, ensuring halal compliance, and achieving long-term economic and ethical objectives in the halal industry.